Clinical and diagnosis value of serum Cortisol, TNF-α, albumin in ovarian cancer patients: Cortisol, TNF-α, albumin in ovarian cancer - Jiang, Rong; Pan, Xin; Shi, Xiu; Zhou, Jinhua; Wang, Juan; Zhang, Hong; Ma, Jingjing (Journal of Medical Biochemistry, 2025)
Objective: This research aimed to evaluate the prognostic value of serum serum Cortisol, TNF-α, albumin in selecting treatment methods for advanced ovarian cancer (OC) patients. Methods: A retrospective analysis was conducted on OC patients undergoing surgery at our hospital from June 2022 to June 2024 with complete clinical and pathological data. Patients were categorized into low ALB (< 35 g/L) and normal ALB (≥ 35 g/L) groups based on pretreatment serum ALB levels. Each group was further divided into primary debulking surgery (PDS) and neoadjuvant chemotherapy followed by interval debulking surgery (NACT-IDS) subgroups. Clinicopathologic characteristics were analyzed. Results: Pretreatment serum ALB levels positively correlated with progression-free survival (PFS) (r = 0.2989, P < 0.05) and overall survival (OS) (r = 0.2702, P < 0.05), with the low ALB group exhibiting significantly lower PFS and OS (P < 0.05). In the low ALB group, significant differences were observed between PDS and NACT-IDS in ascitic fluid level, R0 cytoreduction rate, postoperative complications, and length of stay (P < 0.05), though PFS and OS were comparable (P > 0.05). Similarly, in the normal ALB group, significant differences were noted in FIGO staging, ascitic fluid level, hemoglobin (HGB) levels, intraoperative hemorrhage, blood transfusion volume, R0 cytoreduction rate, and length of stay (P < 0.05), while PFS and OS remained unaffected by treatment type (P > 0.05). Additionally, C-reactive protein (CRP) levels were significantly higher in the low ALB group (6.5 ± 1.1 mg/L vs. 5.2 ± 1.0 mg/L, P < 0.05), indicating greater inflammation, whereas HGB levels were significantly lower (110.4 ± 15.8 g/L vs. 118.7 ± 10.5 g/L, P = 0.021), reflecting poorer nutritional status. Tumor necrosis factor-alpha (TNF-α) levels showed a non-significant upward trend (P = 0.058), while cortisol levels were similar between groups (P = 0.073). Conclusion: Selecting NACT-IDS for advanced OC patients with hypoalbuminemia can reduce incidence of postoperative complications and elevate cytoreductive effect. Thus, hypoalbuminemia can serve as a reference indicator for advanced OC patients to choose NACT-IDS.